PH-, thermo- and electrolyte-responsive polymer gels derived from a well-defined, RAFT-synthesized, poly(2-vinyl-4, 4-dimethylazlactone) homopolymer via one-pot post-polymerization modification. (January 2015) - Pei, Yiwen; Sugita, Odilia R.; Quek, Jing Yang; Roth, Peter J.; Lowe, Andrew B.
Graphical abstract: Highlights: Poly(2-vinyl-4, 4-dimethylazlactone) was prepared via RAFT as a reactive precursor. Gels were prepared by reaction with various primary diamine crosslinkers. Gels were modified with small molecule 1° amines to confer stimuli-responsiveness. Functional gels exhibited pH, temperature or salt responsive (de)swelling behavior. Abstract: Well-defined stimulus-responsive polymer gels were prepared from poly(2-vinyl-4, 4-dimethylazlatone) (PVDMA) via one-pot post-polymerization modification. VDMA homopolymers were reacted with diamine crosslinking agents and functional 1° or 2° amines to form polymer gels that swelled in organic solvents and, in many cases, aqueous solutions. A series of functional amine reagents, including N, N -dimethylethylenediamine (DMEDA), N, N -diethylethylenediamine (DEEDA), morpholine, 3-morpholinopropylamine (MPPA) and tetrahydrofurfurylamine (THFA), were chosen as functional amines to produce polymer gels containing environmentally sensitive species. 13 C solid-state NMR and FTIR spectroscopic measurements confirmed complete conversion of the reactive scaffolds. pH-dependent swelling behavior at ambient temperature was observed in DMEDA-, DEEDA- and MPPA-modified hydrogels. Kinetic studies showed the swelling behaviors of DMEDA-modified hydrogels were regulated by cross-linker type and concentration in acidic water (pH = 4) at ambient temperature. The swelling ratio of hydrogels modified by DEEDA, MPPA and THFA also depended strongly on temperature, indicating successful synthesis of thermoresponsive gels. Furthermore, the concentration of added sodium sulfate played a significant role with respect to the swelling properties of MPPA-modified hydrogels. These smart materials may be of interest in the biomedical field as well as in other applications.